2018
DOI: 10.1038/s41419-018-1165-x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of FBP1 suppressed Snail-induced epithelial to mesenchymal transition in hepatocellular carcinoma

Abstract: Fructose-1,6-bisphosphatase (FBP1), one of the rate-limiting gluconeogenic enzymes, plays critical roles in several cancers and is treated as a tumour suppressor. However, its role in hepatocellular carcinoma (HCC) is unclear. Here, we demonstrated that FBP1 was significantly inhibited during Snail-induced epithelial to mesenchymal transition (EMT) and tissues in HCC. Restoration of FBP1 expression in HCC cancer cells suppressed EMT phenotype, tumour migration and tumour growth induced by Snail overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
1
34
2
Order By: Relevance
“…Previous studies have shown that FBP1 epigenetic repression is common in several cancers, such as hepatocellular carcinoma (HCC), and colon and non-small cell lung, and breast cancer (Bigl et al, 2008;Chen et al, 2011;Liu et al, 2018). Specifically, in breast cancer cells, histone methyltransferase G9a and DNA methyltransferase DNMT1 are recruited to the FBP1 promoter by Snail, a critical factor in epithelial-to-mesenchymal transitions (EMTs), resulting in increased H3K9me2 and DNA methylation (Dong et al, 2013).…”
Section: Future Directionsmentioning
confidence: 99%
“…Previous studies have shown that FBP1 epigenetic repression is common in several cancers, such as hepatocellular carcinoma (HCC), and colon and non-small cell lung, and breast cancer (Bigl et al, 2008;Chen et al, 2011;Liu et al, 2018). Specifically, in breast cancer cells, histone methyltransferase G9a and DNA methyltransferase DNMT1 are recruited to the FBP1 promoter by Snail, a critical factor in epithelial-to-mesenchymal transitions (EMTs), resulting in increased H3K9me2 and DNA methylation (Dong et al, 2013).…”
Section: Future Directionsmentioning
confidence: 99%
“…Notably, HCC patients with high Snail but low FBP1 expression were identified with the worst prognosis. Conversely, patients with low Snail but high FBP1 expression were identified with the best prognosis (67).…”
Section: Discussionmentioning
confidence: 95%
“…FBP1 is a gluconeogenic enzyme that is upregulated in response to fructose exposure [33]. Clinical research has shown that low FBP1 expression is associated with poorer survival and more aggressive HCC growth [119][120][121][122][123][124]. Low FBP1 expression enhances glycolysis in HCC [122,124], while increasing FBP1 reduced GLUT1 expression, glucose uptake, lactate production, and cell growth [120,121,123].…”
Section: Genetic Changes Associated With Hcc May Reduce Fructose Metamentioning
confidence: 99%